НАШИ ХУДОЖНИКИ-КЛАССИКИ И ТВОРЧЕСТВО М.А.САБИРА - Улдуз Фархад Кахраманова (Research Focus International Scientific Journal, 2024)
M.A. Sabir's methods of benefiting from the classical heritage are diverse. In classical poetry, he presents the sufferings of the lyrical hero on his way to his lover and the resulting complaints to the reader in a satirical way. As a result, the lyrical lover turns into a satirical type, and the essence of his suffering turns from sublimity to greed and gluttony. Or that the lover is shot here is not any nice. His lover is science and education, school and madrasa. The father also tries to prevent his child from actually progressing and developing. Because his son fell in love with the "fairy" of science and education, the "angel" of progress and development. This love does not take him to the desert like Majnun, but to a bright tomorrow, to the future. The father's attempt to dissuade his child from this path stems either from ignorance or from being an enemy of progress. Or the lyrical hero in classical literature is ready to make any kind of sacrifice for the lover he loves with his whole being. Because in his eyes, his lover is more beautiful than all the beauties, more subtle than all the subtleties. That's why he addresses her with all kinds of elegant epithets. Sabir's satirical style is focused on vara, money, and food. He is ready for all kinds of evil, greed and cruelty to collect wealth, state, money and gold. Money, gold, wealth from all holy concepts - Mecca, Medina, Qibla, etc. considers superior. Thus, M.A. Sabir changes the nature of the lyrical hero, his parents, and his lover. The reader faces a completely new hero, a new socio-moral environment, a new lover. He meets those heroes in everyday life and "converses" with them. As a result, he was able to present the modern and innovative qualities of the classical heritage to the reader in a new way. The poet's initial acquaintance with classical heritage as a child continued his respect, reverence and creative attitude throughout his life. Also, those relations have developed in a rising and constantly maturing line. M.A. Sabir sometimes directly benefited from the classical heritage, i.e. he made compensation, parodied some of their works, or wrote an allusion and simile, and sometimes he generally tried to preserve the historical memory and restore it in a new quality. In general, M.A. Sabir gained fame as an innovator and a poet with original creativity in the history of Azerbaijani literature. While rising to this peak, he benefited from the classical heritage with artistry and strengthened his voice with the breath and voice of his predecessors. While benefiting from the classics, M.A. Sabir was able to skillfully combine the drama in the core of their works with the creative experience of the national dramaturgy with the drama of the time. All this ensured that his poetry appeared in a dramatic quality.